(untitled) (Scientific journal of the Fergana State University, 2023)
This article is dedicated to Fakhri Kharavi’s scientific work by the name of “Javahir-ul-ajaib”, which is a rich literary heritage and the first tazkire about the prominent women of Central Asia and Middle East. It also provides interesting facts about tazkire manuscripts kept in different libraries of the world.